The importance of values in evidence-based medicine - Kelly, Michael P. (BMC Med Ethics, 2015)
BACKGROUND: Evidence-based medicine (EBM) has always required integration of patient values with ‘best’ clinical evidence. It is widely recognized that scientific practices and discoveries, including those of EBM, are value-laden. But to date, the science of EBM has focused primarily on methods for reducing bias in the evidence, while the role of values in the different aspects of the EBM process has been almost completely ignored. DISCUSSION: In this paper, we address this gap by demonstrating how a consideration of values can enhance every aspect of EBM, including: prioritizing which tests and treatments to investigate, selecting research designs and methods, assessing effectiveness and efficiency, supporting patient choice and taking account of the limited time and resources available to busy clinicians. Since values are integral to the practice of EBM, it follows that the highest standards of EBM require values to be made explicit, systematically explored, and integrated into decision making. SUMMARY: Through ‘values based’ approaches, EBM’s connection to the humanitarian principles upon which it was founded will be strengthened.